Impact of the Libya Crisis on the Tunisian Economy - World Bank (World Bank, Washington, DC, 2017)
This study assesses the main spillover effects of the Libyan crisis on the Tunisian economy and estimates the crisis’ overall social welfare and fiscal impacts on Tunisia. The authors consider four main effects on Tunisia: (i) the increased presence of Libyans in Tunisia (both short- and long-term), and the return of Tunisian workers from Libya; (ii) the level and dynamics of illicit informal trade and informal cash flows between the two countries; (iii) the deterioration of civil security in the region and its effects on private investment and tourism; and (iv) the increase in the Tunisian government’s security spending. The chapter is organized as follows. Section one describes the objectives of the investigation and methodology. Section two estimates the number of Libyans living in Tunisia (temporary and permanent) and their demographic characteristics. Section three analyzes the living conditions of Libyan households in Tunisia and provides an estimate of their poverty level. Section four analyzes the shocks to Libyan households, and those households’ adaptations and resilience in response to shocks. Section five discusses the migratory decisions of Libyan households, in particular their preference to either return to Libya or remain permanently in Tunisia.